Sistem Informasi Pelaksanaan Zakat di Masjid Al-Khair Kota Bengkulu - Muthi, Marsa Hulwa Indri; Luthfi, Irfan; Oktoeberza, Widhia KZ (Rekursif: Jurnal Informatika, 2023)
Zakat, as a fundamental pillar in Islam, plays a crucial role in maintaining the social and economic well-being of the Muslim community. Despite the transformation of societal behavior in the era of digitalization, the utilization of technology in the execution of zakat remains limited. In Masjid Al-Khair, Bengkulu City, challenges related to financial information and low awareness of charitable contributions pose issues. This research proposes a solution in the form of a mosque information system. This system is designed to facilitate the community in contributing to zakat and enhance the financial transparency of the mosque, bridging the gap between needs and limitations in the digital era. It is hoped that the implementation of this website system will boost community participation, provide easily accessible information, and promote transparency and efficiency in zakat activities in the digital era.